ANALYSIS OF ACHIEVEMENT DEVELOPMENT FOR SPECIFIC SPORT CLASSES IN THE SOCCER BRANCH OF SMPN 1 SURAKARTA IN 2020 - Erick Ibrahim; Teguh Santosa; Shodiq Hutomono, (Journal Of Indonesia Sport Education and Adapted Physical Education (JISEAPE), 2022)
This study aims to describe the KKO football team coaching program at SMPN 1 Surakarta, related to the characteristics of athletes, characteristics of coaches, characteristics of the organizing organization, characteristics of programs and strategies for achievement development, characteristics of achievement coaching training programs, characteristics of facilities and infrastructure, characteristics of funding, selection athletes and coaches, training processes, monitoring and evaluation of exercises, and organizing. This research is an evaluative study using the Context, Input, Process, and Product (CIPP) model proposed by Stufflebeam. The data source of this research is a source that can provide information about the coaching program in special sports classes, especially soccer. The sampling technique used was Quota Sampling. The data collection techniques used were observation, interview, documentation and analysis. The data analysis technique used in this study is a non-statistical qualitative analysis method, where the data reduction component and data presentation are carried out simultaneously with the data collection process after the data is collected.There are two conclusions from this research. The input domain for the highest suitability assessment is in the sub-variable Characteristics of the achievement coaching training program, the highest appropriate assessment is in the sub-variable Characteristics of programs and achievement development strategies, the highest unsuitable assessment is in the sub-variable Characteristics of funding, and the assessment is not the highest according to the athlete's Characteristics sub variable. Whereas in the realm of the highest suitability assessment process is in the training process sub variable, the highest appropriate assessment is in the Organizing sub-variable, the highest unsuitable assessment is in the athlete selection sub-variable sub-variable and the training and evaluation monitoring and evaluation sub-variable, and the highest non-conforming assessment is on the training process variable and exercise monitoring and evaluation sub variables.